Improving lead times for life insurance products and services offered by tied financial advisors at company X - Mogale, Elnorah Lebang (My University, 2024)
Life insurance provides the family with security in the unfortunate event that the policyholder passes away. In order for insurers to remain competitive and profitable in today's fast-paced business environment, which is driven by consumers who have less patience with time-consuming processes, policy issuance lead times must be reduced. The purpose of this research was to evaluate the different approaches to reduce the lead times of product and service delivery at Life Insurance Company X. Existing lead times must be decreased if the company wants to grow its market share in the mass market. Despite the insurance industry's emphasis on client-centricity and the importance of issuing policies as quickly as possible, little attention has been paid to the concept of lead times and their reduction. The study used a qualitative research design, with a sample of Life Insurance X employees being interviewed and observed. The mapping tools used in the study were guided by the results of the interviews and observations, which aided in the identification of value-adding, non-value-adding, and non-valueadding but required activities. The study demonstrates that addressing the failure demand experienced in the process, ensuring minimal touch points, and ensuring employees spend time productively rather than waiting on office equipment are beneficial to reducing lead times.
A research report submitted in fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2023
Keywords: Life insurance; Policyholder; Service delivery